2023
DOI: 10.4314/rejhs.v11i3.3
|View full text |Cite
|
Sign up to set email alerts
|

Monkeypox related knowledge, attitudes and practices among students in a tertiary institution in southwest, Nigeria: A cross-sectional study

Abstract: Introduction: Monkeypox caused by monkeypox virus, a member of the Orthopoxvirus genus in the family Poxviridae is usually a self-limited disease, however severe cases can occur with case fatality ratio of 3–6% being reported in recent times. This study is aimed at assessing monkeypox related knowledge, attitudes and practices among students in a tertiary institution in Southwest, Nigeria. Methodology: The study utilized a cross-sectional design and semi-structured questionnaire to collect data from 278 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Only 38.5% (95% CI: 32.5–45%) of healthcare workers in this study had good knowledge of mpox. The finding was in line with the studies from Indonesia, 36 Pakistan, 37 Turkey, 38 Lebanon, 40 and Nigeria 39 where 36.5%, 34.4%, 32.5%, 33.7%, and 37.8% of the healthcare workers had good knowledge about mpox respectively. In a similar vein, a study done on the Lebanese general population showed that 33.04% of those surveyed had a good knowledge of mpox.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Only 38.5% (95% CI: 32.5–45%) of healthcare workers in this study had good knowledge of mpox. The finding was in line with the studies from Indonesia, 36 Pakistan, 37 Turkey, 38 Lebanon, 40 and Nigeria 39 where 36.5%, 34.4%, 32.5%, 33.7%, and 37.8% of the healthcare workers had good knowledge about mpox respectively. In a similar vein, a study done on the Lebanese general population showed that 33.04% of those surveyed had a good knowledge of mpox.…”
Section: Discussionsupporting
confidence: 90%
“…A study from Italy indicated that the knowledge status of Italian healthcare workers was quite unsatisfying, with substantial knowledge gaps towards mpox. 34 In a study conducted in Bangladesh, only 30.59%, 35 Indonesia, only 10%, 36 Pakistan, only 34.4%, 37 Turkey, 38 only 32.5%, Nigeria 39 only 37.8% of HCWs had good knowledge regarding the clinical presentation, transmission, and prevention of mpox. Similarly, a study in Lebanon reported low knowledge levels about mpox diagnosis and management among health workers where 33.7% of those surveyed had a good knowledge of mpox.…”
Section: Introductionmentioning
confidence: 99%